Influence the size and quality of chips in the pulping - Camargo, Sâmique Kyene de Carvalho Araujo; Silva, Tiago José da; Costa, Daiane de Moura (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The quality of the chips used in pulp production is considered an important factor for the industry operability and quality of the pulp. Desirable chips are those that have little variations in physical and chemical characteristics, free of contaminants, high bulk density, homogeneous impregnation, polysaccharides low degradation and high performance in the processing of pulp. In manufacturing the chip size classification has been adopted after studies showed that the chip very large and / or too small could interfere in the delignification process and thequality of pulp. The objective of this paper is to present the dimensions and quality of chips for pulping.